Age-related differences in affective responses to and memory for emotions conveyed by music: a cross-sectional study - Vieillard, Sandrine; Gilet, Anne-Laure (Frontiers in Psychology, 2013)
There is mounting evidence that aging is associated with the maintenance of positive affect and the decrease of negative affect to ensure emotion regulation goals. Previous empirical studies have primarily focused on a visual or autobiographical form of emotion communication. To date, little investigation has been done on musical emotions. The few studies that have addressed aging and emotions in music were mainly interested in emotion recognition, thus leaving unexplored the question of how aging may influence emotional responses to and memory for music. In the present study, eighteen older (60-84 years) and eighteen younger (19-24 years) listeners were asked to evaluate the strength of their experienced emotion on happy, peaceful, sad, and scary musical excerpts (Vieillard, et al., 2008) while facial muscle activity was recorded. Participants then performed an incidental recognition task followed by a task in which they judged to what extent they experienced happiness, peacefulness, sadness, and fear when listening to music. Compared to younger adults, older adults (a) reported a stronger emotional reactivity for happiness than other emotion categories, (b) showed an increased zygomatic activity for scary stimuli, (c) were more likely to falsely recognize happy music, and (d) showed a decrease in their responsiveness to sad and scary music. These results are in line with previous findings and extend them to emotion experience and memory recognition, corroborating the view of age-related changes in emotional responses to music in a positive direction away from negativity.